PELATIHAN PERCOBAAN SAINS SEDERHANA UNTUK ANAK USIA DINI PADA GURU PAUD DI TK SARI MEKAR KOTA TERNATE - Sahidun, Nurfitri; Haryati, Haryati; Rahayu, Puji Dwi; Sapil, Nursin (Kreasi: Jurnal Pengabdian Masyarakat, 2023)
Simple Science Experiment Training for early childhood children for PAUD teachers was carried out based on the results of initial observations, namely the teacher's lack of knowledge about science activities or activities that can stimulate the development of early childhood children, especially cognitive ones. This activity aims to provide information and practice directly to teachers and children about simple science experiments with children. The method used in this service activity is the PAR (Participatory Action Research) method. When carrying out simple science experiment activities, teachers and children take part in the process of observing, discussing changes that occur in the process of simple science experiments, drawing conclusions and providing motivation to each other in science experiment activities